Using Folklore Videos and Small Group Discussions in Teaching Written Narrative Text at Islamic Senior High School - Laili Shidqiyah; Ngasbun Egar; Maria Yosephin WL (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The aim of this research is (1) to find out the writing ability taught using folklore videos without small group discussion, (2) to find out the writing ability taught using folklore videos and small group discussion, (3) to find out whether any significant difference writing abilities of the eleventh-grade students of MA Abwabun Nurul Maghfiroh Mranggen Demak taught using folklore videos without small group discussion and those taught using folklore videos and small group discussion. In this research, quantitative was applied to analyze data, including a control class and experimental class in eleventh-grade students of MA Abwabun Nurul Maghfiroh Mranggen Demak 2023. Quantitative research requires the researcher to determine the significant relationship between the independent and dependent variables. In this study, the researcher attended two classes: one was an experimental class taught using folklore videos complemented with small group discussion, and the other was a control class taught using folklore videos without small group discussion. This research uses statistics to analyze statistical data formulas, specifically SPSS. The results showed that (1) the Writing ability of the students taught using folklore videos without small group discussion showed that the mean score on the pretest was 67.93 (Good Level) and the mean score on the post-test was 75,34 (Good level) and then (2) Writing ability of the students taught using folklore videos and small group discussion showed that was means score of the pretest was 64.47 (Good Level), and post-test was 81.83 (Excellent Level) and (3) Difference of Writing ability in narrative text taught using folklore videos without small group discussion and taught complemented small group discussion. Based on the SPSS 2.6 normality test, the researcher can determine that the Kolmogorov-Smirnov and Saphiro-Wilk tests provide two values of Sig > 0.05. As a result, the researcher might conclude that H0 cannot be accepted and that the data do not belong to a normal distribution. Thus, the researcher must identify significant differences using the Mann-Whitney U and Wilcoxon tests. The results of the Wilcoxon test (The value of Asymp. Sig (2-tailed) is found to be 0.000) and Mann Whitney test (Asymp. Sig (2-tailed) is worth 0.002 less than 0.05). The result is significant and effective.